The epidemiology and prevention of noise-induced hearing loss (NIHL) in New Zealand. (19th October 2011) - Laird, Ian; McBride, David
Abstract : Objectives: The epidemiology of NIHL in New Zealand is poorly understood and more information is needed to identify effective strategies to prevent hearing loss. The objective was to review the current epidemiology of NIHL in New Zealand and examine noise sources, exposures and the effectiveness of existing noise control strategies in small to medium sized enterprises. Methods: Modelling was undertaken to predict rates of noise exposure and thus of the prevalence of noise induced hearing loss in different occupations and economic sectors in New Zealand industry. A case study design was utilised to identify, describe and evaluate noise sources, exposures and control strategies used by "high", "moderate" and "low" risk industry sectors in relation to exposure to noise. Results: Exposure estimates are presented that question whether the model provides adequate approximations to levels of occupational noise exposure in New Zealand workplaces. Thirty three (33) small business workplaces were assessed, which showed that generally noise sources and paths could be readily identified and that area and personal sound level exposure measurements varied considerably between the high, moderate and low risk industry sectors. The predominant noise control strategy used by small businesses was the use of personal hearing protection. Most enterprises surveyed did not conform to the specific requirements of legislative standards for noise management. Conclusions: The findings suggest that the regulatory priority given to personal protection and hearing conservation programmes needs to be re-evaluated and that there needs to be significant changes in expectations with respect to policing the requirements of noise legislation.